2014
DOI: 10.1002/jsfa.6908
|View full text |Cite
|
Sign up to set email alerts
|

Mutation breeding of Saccharomyces cerevisiae with lower methanol content and the effects of pectinase, cellulase and glycine in sugar cane spirits

Abstract: Mutagenesis of UV coupled with DES is an efficient way to generate a mutant of S. cerevisiae with lower methanol content. Also, it is necessary to control the additions of pectinase, cellulase and glycine in the fermentation medium, and other unknown ways to generate methanol metabolic pathway in yeasts may need further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In the suitable temperature range for yeast to grow, the methanol content also showed a corresponding increasing trend (except low temperature steeping fermentation) with the increase of temperature. This was in agreement with the findings of previous research (Liang et al, 2014b). The methanol content exceeded the safety limit of 400 mg/L when the temperature was above 30°C.…”
Section: Different Fermentation Conditionssupporting
confidence: 93%
“…In the suitable temperature range for yeast to grow, the methanol content also showed a corresponding increasing trend (except low temperature steeping fermentation) with the increase of temperature. This was in agreement with the findings of previous research (Liang et al, 2014b). The methanol content exceeded the safety limit of 400 mg/L when the temperature was above 30°C.…”
Section: Different Fermentation Conditionssupporting
confidence: 93%
“…About 0·5 ml Na 2 S 2 O 3 was added to 1 ml bacterial suspension and the reaction was terminated at 10 min (Liang et al . ). Subsequently the reaction suspension was diluted and then spread on the plate, each with three replicates.…”
Section: Methodsmentioning
confidence: 97%
“…Mutagenesis by ultraviolet (UV) coupled with diethyl sulphate (DES) was used to generate a mutant of Saccharomyces cerevisiae with a lower methanol content (Liang et al . ). A mutant strain, Gluconacetobacter xylinus AX2‐16, was obtained by combined chemical mutation of the parent strain ( G. xylinus CGMCC 2955) with DES and LiCl.…”
Section: Introductionmentioning
confidence: 97%
“…unintentionally produce a small amount of methanol via the decomposition of fruit pectin and yeast glycine metabolism (Liang et al, 2015). Blumenthal et al (2021) suggested that the sugar/pectin ratio during fermentation can affect the methanol content of the finished wine.…”
Section: International Journal Of Food Science and Technology 2023mentioning
confidence: 99%